Clinical application of unilateral intramedullary K-wire occupying technique for flexible reduction in pediatric supracondylar humeral fractures - Wenqiang Xu; Wei Wang; Xiulin Ma; Yongfei Fan; Jianqiang Zhang; Chaoyu Liu; Haiyang Yu (Frontiers in Surgery, 2026)
Objective To investigate the clinical efficacy of unilateral Kirschner wire (K-wire) intramedullary occupying technique for flexible reduction combined with ultrasound guidance in the treatment of pediatric supracondylar humeral fractures. Methods A retrospective analysis was conducted on 41 patients with Gartland type III and IV pediatric supracondylar humeral fractures treated in our hospital from January 2024 to April 2025. Among them, 21 patients underwent closed reduction assisted by the unilateral K-wire intramedullary occupying technique (observation group), and 20 patients received traditional closed reduction (control group). No statistically significant differences were observed between the two groups in age, sex, injury cause, fracture side, Gartland classification, or time from injury to surgery ( P > 0.05). Operative time, intraoperative fluoroscopy frequency, fracture healing time, complication rate, and elbow function assessed by Flynn score, Baumann angle, and carrying angle at the last follow-up were compared between the two groups. Results All fractures in both groups underwent ultrasound-guided closed reduction. The observation group had significantly shorter operative time and fewer intraoperative fluoroscopic acquisitions than the control group ( P < 0.05). All patients were followed up for 12–24 months (data cutoff: May 31, 2026), and imaging showed fracture healing in both groups, with no significant difference in healing time ( P = 0.920). At the last follow-up, the Flynn score indicated an excellent/good rate of 100% in both groups. No significant differences were found between the healthy and affected sides in Baumann angle or carrying angle in either group ( P > 0.05). Pin site irritation occurred in 4 cases in the observation group and 3 cases in the control group, with no significant difference ( P = 1.000). Conclusion For pediatric Gartland type III and IV supracondylar humeral fractures with significant lateral displacement, both ultrasound-guided closed reduction techniques achieve satisfactory clinical outcomes. However, the unilateral K-wire intramedullary occupying technique is relatively simpler, with shorter operative time and fewer fluoroscopic acquisitions, making it a viable surgical option for such fractures.